2010
DOI: 10.1029/2009rs004345
|View full text |Cite
|
Sign up to set email alerts
|

Probability density function estimation for characterizing hourly variability of ionospheric total electron content

Abstract: [1] Ionospheric channel characterization is an important task for both HF and satellite communications. The inherent space-time variability of the ionosphere can be observed through total electron content (TEC) that can be obtained using GPS receivers. In this study, within-the-hour variability of the ionosphere over high-latitude, midlatitude, and equatorial regions is investigated by estimating a parametric model for the probability density function (PDF) of GPS-TEC. PDF is a useful tool in defining the stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…In Deviren et al (), it has been shown that a midlatitude region of size 10° × 20°, in latitude and longitude, respectively, can best be represented by a planar trend. Also, in Turel and Arikan (), the probability density functions of TEC can be optimally categorized when regions of 10 in latitude are considered.…”
Section: Introductionmentioning
confidence: 99%
“…In Deviren et al (), it has been shown that a midlatitude region of size 10° × 20°, in latitude and longitude, respectively, can best be represented by a planar trend. Also, in Turel and Arikan (), the probability density functions of TEC can be optimally categorized when regions of 10 in latitude are considered.…”
Section: Introductionmentioning
confidence: 99%
“…[]; Karatay et al . []; Turel and Arikan , []; and Foster and Evans []. Thus, it is an important task to interpolate the missing TEC values within a day or for a whole day.…”
Section: Introductionmentioning
confidence: 99%
“…The variability of TEC directly reflects the variability in electron density profile, which is a complicated function of position, height, and time. In recent decades, the worldwide, dual-frequency GPS receivers provide a cost-surveying, and monitoring of SW require continuous operation of GPS receivers and uninterrupted TEC estimation for 24 h. The continuous data sets are used in modeling of ionosphere, TEC mapping, computerized ionospheric tomography (CIT), within-the-hour statistical analysis, ionospheric earthquake precursor studies, and prediction of SW events such as those provided in Erturk et al [2009]; Karatay et al [2010]; Turel and Arikan, [2010]; and Foster and Evans [2008]. Thus, it is an important task to interpolate the missing TEC values within a day or for a whole day.…”
Section: Introductionmentioning
confidence: 99%
“…That is the most positively disturbed day in August where Kp and Dst indices for that day indicate that there is a sudden commencement of a geomagnetic storm. The experimental hourly probability density functions (pdf) for some GPS reference station sites are investigated according to the method presented in [5] between 2001 and 2008, and it is been observed that yearly pdf distributions are Weibull distributed for hours that correspond to sunrise and sunset. Other hours are Lognormally distributed.…”
Section: Regional Space-time Parametric Modeling Of Ionospherementioning
confidence: 99%